COMPARISON OF OPERATIVE COMPLICATIONS OF DIRECT TROCAR ACCESS VERSUS VERESS NEEDLE INSERTION TECHNIQUE FOR INITIAL PERITONEAL ENTRY IN PATIENTS UNDERGOING GYNECOLOGICAL LAPAROSCOPIC SURGERY - Amna Rafiq,; Zafar, Al Fareed; Maryam Javed,; Mehwish Ilyas,; Saima Saeed Usmani,; Rizwana Tariq, (Journal of Ayub Medical College Abbottabad, 2021)
Background: Laparoscopy is considered to be a good diagnostic and surgical way to replace open surgeries in all surgical fields. As it is a least invasive method, with advantages for patients and all associated with medical care. There is a significant increase in the use of laparoscopic surgery in gynecology. This study was done to compare the frequency of operative complications of direct trocar access versus Veress needle insertion technique for initial peritoneal entry in patients undergoing gynecological laparoscopic surgery. Methods: This Randomized Controlled Trial was conducted at the Department of Obstetrics & Gynecology, Lahore General Hospital, Lahore from 26-12-2019 to 25-6-2020. Four hundred consecutive patients were enrolled and divided randomly into two groups by blocked randomization. Direct trocar insertion (DTI) technique was used for initial peritoneal access in group A and Veress needle (VNI) was inserted first for peritoneal access in group B. Results: The mean age of the patients in DTI group was 35.76±8.38 years whereas that in VNI group was 35.85±8.38 years. In DTI group there were 8(4%) patients with extra-peritoneal insufflation and in VNI group there were 19(9.5%) patients with extra-peritoneal insufflation. There were 8(4%) patients in DTI group with Omental injury and VNI group there were 13(6.5%) patients with Omental injury. In DTI group there were 7(3.5%) patients with port-site infection compared to 15(7.5%) in VNI group. Conclusion: According to findings the rate of complications observed with VNI, DTI can be a preferred procedure for gynecological surgeries.